Training with draught animals - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
A new agreement has been signed between the government of Cameroon and the West German Agency for Technical Co-operation, to extend the 'Wum area oxen farming project' in the mountainous northwest of Cameroon The project was set up in 1976 to offer...